Does a Cognitive Conflict-Based Physics Website Integrated with Augmented Reality and STEM Improve Critical Thinking and Remediate Misconceptions on Two-Dimensional Motion? - Indah Zalsabila; Fatni Mufit; Emiliannur Emiliannur; Hidayati Hidayati; Yeka Hendriyani; Zahra Fathanah (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Critical thinking and conceptual understanding are essential competencies in physics learning, yet students still experience low critical thinking skills and high levels of misconceptions, particularly in two-dimensional motion topics. This research sought to evaluate the extent to which an augmented reality (AR) and STEM integrated cognitive conflict-based physics website contributes to the development of critical thinking skills and the correction of misconceptions in two-dimensional motion concepts. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent pretest-posttest control group design. The participants were 63 tenth-grade students of SMAN 2 Lubuk Sikaping, including 32 students in the experimental group and 31 students in the control group. A validated and reliable four-levels multiple-choice test was employed to collect data on critical thinking abilities and misconceptions concurrently. Descriptive statistics and the Mann–Whitney U test were employed to analyze the collected data. The results showed that the experimental class achieved a higher mean posttest score in critical thinking skills (64,3) than the control class (39,1). The Mann–Whitney test showed a significant difference between the two groups (p < 0.05). In addition, the percentage of misconceptions in the experimental class decreased from 80.0 to 46.0, while the control class showed only a slight reduction. The results of the study show that the AR-STEM integrated cognitive conflict-based physics website effectively improves critical thinking skills and corrects misunderstandings in two-dimensional motion learning. Therefore, the website can serve as an innovative learning resource to support meaningful physics learning and conceptual change.